Aerodynamic characteristic comparison of ultra-highly and normally loaded fans. (November 2021) - Cao, H.; Zhou, Z.G; Ye, X.L.
ABSTRACT: To reduce fan noise and weight, according to the structural characteristics of a turbofan engine, a fan rotor with an ultra-low rotating speed is designed in this study by using a new concept of diffusion blade profiles in which the rotating speed of an ultra-highly loaded rotor is only 0.58 times that of a normally loaded rotor. To further examine the applicability of this rotor, its matching stator is also designed. The flow fields in the ultra-highly and normally loaded fan stages are simulated using the same numerical method to conduct an aerodynamic characteristic comparison. Compared with the normally loaded rotor, the sizes of the boundary layers on the blade surfaces, the wakes behind the blades and the flow losses of the ultra-highly loaded rotor are smaller. At the design point, the efficiency of the ultra-highly loaded fan stages is higher than that of the normally loaded stage; moreover, the surge margin of the former is evidently larger than that of the latter. The ultra-highly loaded fan could be a good candidate for use in Ultra-High Bypass Ratio Geared Turbofan (UHBRGT) technology.